Produção e caracterização de matriz carbonácea á base de amido de mandioca - Lopes, Nicole Dall'Accua (2024)
Carbonaceous matrix is defined as material that is rich in carbon. The carbonaceous matrix used in the present study has the characteristic of being porous, that is, it has empty spaces in its structure. These pores are necessary with a fluid, which can be liquid or gas. With this in mind, recent objective studies will replace high-quality commercial porous carbon with common activated carbon, which is extracted from carbon-rich natural sources. An alternative material for this production is starch, which is a natural, cheap and renewable biopolymer, in addition to being rich in carbon. In this way, it presents itself as an excellent alternative for the production of carbonaceous matrix, which occurs through gelatinization, retrogradation and thermal manipulation processes. Therefore, the present work aims to develop and characterize the carbonaceous matrix, obtained from cassava starch. Furthermore, the hydrolysis process of different nickel salts in the porous matrix was analyzed, namely: nickel nitrate, nickel sulfate and nickel chloride. The materials were analyzed using Raman spectroscopy, infrared with Fourier transformed spectroscopy and X-ray diffraction. With this, it was possible to observe that the sample that most resembled the starch sample was the one with nickel nitrate, after carbonization. In addition, it can be noted that the crystalline domain of the materials did not change, only the amorphous domain of the structures as affected throughout the hydrolysis.